One-pot method for preparing high-strength, flame-retardant organic-inorganic nanohybrid fiber membranes
The nanocellulose and organic-inorganic nanohybrid fiber membranes were prepared simultaneously by treating cellulose and vermiculite under microwave-ultrasound conditions by one pot method, which solved the problems of complex preparation process and low efficiency in the prior art, and achieved high Efficient preparation of nanocellulose and organic-inorganic nanohybrid fiber membranes with strength and flame retardant properties.
Patent Information
- Application Number
- CN202211481629.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-24
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-11-24
AI Technical Summary
The existing nanocellulose and its organic-inorganic nanohybrid fiber membrane materials preparation methods have problems such as complex process, low efficiency, long production cycle and difficulty in separation and purification of intermediate products, which hinder the large-scale production and application of materials.
The one-pot method is used to colloid grind and pretreat the thermally expanded vermiculite and cellulose raw materials in microwave-ultrasonic reaction to form a nanovermiculite solution, and then add hydrochloric acid solution for microwave-ultrasonic reaction to prepare nanocellulose and organic-inorganic nanos. Hybrid fiber membranes simplify the preparation process and improve efficiency.
The high yield of nanocellulose and the high strength and flame retardant properties of organic-inorganic nanohybrid fiber membranes are achieved, the preparation process is simplified, the production efficiency is improved, and the problems of cumbersome steps and low efficiency in traditional methods are solved.
Smart Images

Figure CN115652698B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of natural polymer materials, and in particular relates to a method for preparing a high-strength, flame-retardant organic-inorganic nano hybrid fiber membrane by a one-pot process. Background Art
[0002] At present, the main methods for preparing nanocellulose are acid hydrolysis, physical method and enzymatic method, but there are still some problems that have not been solved, which restrict the large-scale production of nanocellulose. For example, a large amount of waste liquid is generated during the acid hydrolysis process, which is difficult to post-process, causes serious corrosion to the equipment, and has high production costs; the physical method requires customized high-pressure homogenization, shearing or grinding equipment, which is costly, energy-intensive, and has low nanofiber yields; the enzymatic method has a low yield, a long production cycle, harsh reaction conditions, and is difficult to mass produce. Vermiculite can be formed into nano-vermiculite after mechanical peeling, which has cation exchange properties and catalytic effects after acid treatment. Compared with vermiculite, it has a larger specific surface area and porosity, a low thermal conductivity, and has thermal insulation and fireproof properties. Therefore, the use of nano-vermiculite for the hydrolysis of cellulose is expected to prepare nanocellulose in a green and efficient manner and promote the large-scale production of nanocellulose.
[0003] At present, the preparation of cellulose-based organic-inorganic nano-hybrid fiber membranes usually requires the preparation of nanocellulose and inorganic nanoparticles separately, and then the composite formation of organic-inorganic nano-hybrid materials. The entire preparation process is cumbersome, the operation is complicated, the separation and purification of intermediate products is difficult, the efficiency is low, and the production cycle is long, which hinders the development and application of organic-inorganic nano-hybrid fiber membranes. Therefore, the development of new preparation methods for nanocellulose and its organic-inorganic nano-hybrid fiber membrane materials, the improvement of nanocellulose yield and the performance of organic-inorganic nano-hybrid fiber membrane materials, the simplification of the preparation process, and the concentration of complex multi-step reaction processes in a "one-pot" are the key to realizing the large-scale production of nanocellulose and its organic-inorganic nano-hybrid fiber membrane materials. Summary of the invention
[0004] In order to solve the shortcomings of the existing methods for preparing nanocellulose and organic-inorganic nanohybrid fiber membrane materials, the present invention provides a method for preparing high-strength and flame-retardant organic-inorganic nanohybrid fiber membranes in one pot directly using plant crude fiber as raw material. The method has simple operation steps and high efficiency, reduces the complicated and time-consuming intermediate product separation process, realizes the simultaneous preparation of nanocellulose and construction of organic-inorganic nanohybrid fiber membranes, has a high nanocellulose yield, and the organic-inorganic nanohybrid fiber membranes have high mechanical strength and good flame retardant properties.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] The one-pot method for preparing high-strength, flame-retardant organic-inorganic nano-hybrid fiber membranes comprises the following steps:
[0007] (1) adding heat-expanded vermiculite to a saturated sodium chloride solution for colloid mill pretreatment for a certain period of time, taking out the sample and adding a certain concentration of hydrochloric acid solution for microwave-ultrasonic reaction to obtain a nano-vermiculite solution;
[0008] (2) adding cellulose raw material to the nano-vermiculite solution obtained in step (1), adjusting the reaction temperature, and continuing the microwave-ultrasonic reaction for a certain period of time to obtain nano-cellulose, and uniformly dispersing the collected reaction products by ultrasonication without separation to form a nano-vermiculite / nano-cellulose mixed solution;
[0009] (3) The nano-vermiculite / nano-cellulose mixed solution obtained in step (2) is transferred into a culture dish for injection molding, and placed in a constant temperature and humidity chamber to dry into a film. The formed film is immersed in deionized water and repeatedly rinsed to remove inorganic salt ions, and naturally dried at room temperature to obtain an organic-inorganic nano-hybrid fiber membrane.
[0010] Furthermore, in step (1), the solid-liquid ratio of the heat-expanded vermiculite to the saturated sodium chloride solution is 1:25-1:50 g / mL, the rotation speed of the colloid mill is 10000-13000 rpm, and the pretreatment time of the colloid mill is 6-11 hours.
[0011] Furthermore, in step (1), the concentration of the hydrochloric acid solution is 0.1-0.5 mol / L, the solid-liquid ratio of the heat-expanded vermiculite to the hydrochloric acid solution is 1:60-1:80 g / mL, the microwave power is 600 W, the ultrasonic power is 800 W, the microwave-ultrasonic reaction time is 9 h, and the reaction temperature is 120° C.
[0012] Furthermore, the cellulose raw material in step (2) is any one of coniferous wood pulp, broadleaf wood pulp, and bamboo pulp, the solid-liquid ratio of the cellulose raw material to the nano-vermiculite solution is 1:25-1:50 g / mL, the microwave-ultrasonic reaction time is 4 hours, the reaction temperature is 100° C., the microwave power is 500 W, and the ultrasonic power is 800 W.
[0013] Furthermore, in step (3), the constant temperature and humidity are 50° C., 50% humidity, and 24 hours of drying time.
[0014] Significant advantages of the present invention
[0015] (1) The present invention utilizes the catalytic effect, cross-linking effect and heat insulation and fireproof properties of nano-vermiculite to prepare nano-cellulose and its organic-inorganic nano-hybrid fiber membrane in one pot, thus solving the technical problems of the traditional preparation method, which is complicated, cumbersome, time-consuming and inefficient;
[0016] (2) The present invention utilizes the catalytic effect of nano-vermiculite to hydrolyze cellulose to obtain nano-cellulose. The entire reaction system is not separated. Nano-vermiculite acts as a cross-linking agent and a reinforcing agent to form a strong hydrogen bond with nano-cellulose, forming a high-strength organic-inorganic nano-hybrid fiber membrane in one pot. The interlayers of nano-vermiculite are opened more completely, the specific surface area is increased, the heat absorption is enhanced, the thermal conductivity is reduced, and the thermal insulation and fireproof properties of vermiculite are significantly improved. Therefore, the organic-inorganic nano-hybrid fiber membrane can be endowed with excellent flame retardant properties.
[0017] (3) The preparation process of the present invention is simple and efficient, and the preparation of nanocellulose and the construction of organic-inorganic nanohybrid fiber membrane are carried out simultaneously. The nanocellulose yield is high, and the organic-inorganic nanohybrid fiber membrane has high mechanical strength and good flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a transmission electron microscopy image of the nanocellulose prepared in Example 1;
[0019] Figure 2 This is a scanning electron microscope image of the organic-inorganic nanohybrid fiber membrane prepared in Example 2. DETAILED DESCRIPTION
[0020] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0021] Example 1
[0022] (1) 4 g of heat-expanded vermiculite was added to 150 mL of saturated sodium chloride solution, and the mixture was pretreated in a colloid mill at 12,000 rpm for 8 h. After the pretreatment, 250 mL of 0.3 mol / L hydrochloric acid solution was added, and the mixture was transferred to a microwave-ultrasonic reactor. The reaction time was 9 h under the conditions of microwave power of 600 W, ultrasonic power of 800 W, and temperature of 120 ° C to obtain a nano-vermiculite solution;
[0023] (2) Add 2 g of bleached fir pulp into 60 mL of nano vermiculite solution, under the conditions of reaction temperature of 100 °C, microwave power of 500 W, ultrasonic power of 800 W, and microwave-ultrasonic reaction time of 4 h to obtain nanocellulose. The reaction product is ultrasonically dispersed to form a nano vermiculite / nanocellulose mixed solution;
[0024] (3) The nano-vermiculite / nano-cellulose mixture was transferred into a culture dish for injection molding, and dried for 24 hours in a constant temperature and humidity chamber at 50°C and 50% humidity to form a membrane. The formed membrane was immersed in deionized water and rinsed repeatedly to remove inorganic salt ions, and then dried naturally at room temperature to obtain an organic-inorganic nano-hybrid fiber membrane.
[0025] The yield of the obtained nanocellulose is 89%, the diameter is 10-20nm, the length is 100-300nm, and the transmission electron microscope image is as follows Figure 1 shown.
[0026] Example 2
[0027] (1) 2 g of heat-expanded vermiculite was added to 60 mL of saturated sodium chloride solution, and the mixture was pretreated in a colloid mill at 11000 rpm for 6 h. After the pretreatment, 150 mL of 0.5 mol / L hydrochloric acid solution was added, and the mixture was transferred to a microwave-ultrasonic reactor. The reaction time was 9 h under the conditions of microwave power of 600 W, ultrasonic power of 800 W, and temperature of 120 ° C to obtain a nano-vermiculite solution;
[0028] (2) Add 2 g of bleached bamboo pulp into 80 mL of nano-vermiculite solution, under the conditions of reaction temperature of 100 °C, microwave power of 500 W, ultrasonic power of 800 W, microwave-ultrasonic reaction time of 4 h, to obtain nanocellulose, and the reaction product is ultrasonically dispersed to form a nano-vermiculite / nanocellulose mixed solution;
[0029] (3) The nano-vermiculite / nano-cellulose mixture was transferred into a culture dish for injection molding, and dried for 24 hours in a constant temperature and humidity chamber at 50°C and 50% humidity to form a membrane. The formed membrane was immersed in deionized water and rinsed repeatedly to remove inorganic salt ions, and then dried naturally at room temperature to obtain an organic-inorganic nano-hybrid fiber membrane.
[0030] The yield of the obtained nanocellulose is 86%, the diameter is 15-30nm, and the length is 200-500nm; the scanning electron microscope image of the formed organic-inorganic nanohybrid fiber membrane is as follows Figure 2 shown.
[0031] Example 3
[0032] (1) 3 g of heat-expanded vermiculite was added to 130 mL of saturated sodium chloride solution, and the mixture was pretreated in a colloid mill at 13,000 rpm for 11 h. After the pretreatment, 200 mL of 0.1 mol / L hydrochloric acid solution was added, and the mixture was transferred to a microwave-ultrasonic reactor. The reaction time was 9 h under the conditions of microwave power of 600 W, ultrasonic power of 800 W, and temperature of 120 ° C to obtain a nano-vermiculite solution.
[0033] (2) 4 g of poplar dissolving pulp was added to 200 mL of nano-vermiculite solution. The reaction temperature was 100 °C, the microwave power was 500 W, the ultrasonic power was 800 W, and the microwave-ultrasonic reaction time was 4 h to obtain nanocellulose. The reaction product was ultrasonically dispersed to form a nano-vermiculite / nanocellulose mixed solution.
[0034] (3) The nano-vermiculite / nano-cellulose mixture was transferred into a culture dish for injection molding, and dried for 24 hours in a constant temperature and humidity chamber at 50°C and 50% humidity to form a membrane. The formed membrane was immersed in deionized water and rinsed repeatedly to remove inorganic salt ions, and then dried naturally at room temperature to obtain an organic-inorganic nano-hybrid fiber membrane.
[0035] The yield of the obtained nanocellulose is 80%, the diameter is 20-30nm, and the length is 300-500nm.
[0036] Comparative Example 1
[0037] (1) 4 g of heat-expanded vermiculite was added to 150 mL of saturated sodium chloride solution and immersed for 8 h, then 250 mL of 0.3 mol / L hydrochloric acid solution was added, and the mixture was heated at 120 °C for 9 h to obtain a vermiculite solution;
[0038] (2) Add 2 g of bleached fir pulp into 60 mL of vermiculite solution. Under the conditions of reaction temperature of 100 °C, microwave power of 500 W, and ultrasonic power of 800 W, the microwave-ultrasonic reaction time is 4 h. After the reaction product is ultrasonically dispersed evenly, it is transferred into a culture dish for injection molding. The film is dried for 24 h in a constant temperature and humidity chamber at 50 °C and 50% humidity to form a film. The formed film is immersed in deionized water and rinsed repeatedly to remove inorganic salt ions. The film is naturally dried at room temperature to obtain an organic-inorganic nano-hybrid fiber membrane.
[0039] The yield of the obtained nanocellulose is 21%, the diameter is 30-50nm, and the length is 500-800nm.
[0040] The performance of the organic-inorganic nano-hybrid fiber membranes prepared in various examples was tested, and the results are shown in Table 1.
[0041]
[0042] As shown in Table 1, the tensile strength and flame retardant properties (reflected by the limiting oxygen index) of the samples of Examples 1-3 are significantly better than those of Comparative Example 1, mainly because the layered structure of the vermiculite in the embodiment is peeled off under the mechanical force chemical action generated by the colloid mill and microwave-ultrasound to form nano vermiculite, and the interlayer of the nano vermiculite is opened more completely, the specific surface area is increased, more reactive sites are exposed, and the catalytic hydrolysis of cellulose is enhanced, so the yield of nano cellulose is high; and the nano-scale nano vermiculite has better dispersibility in the nano cellulose solution, and can produce strong hydrogen bonds with nano cellulose to form a dense organic-inorganic nano hybrid fiber membrane structure, which significantly improves the mechanical properties of the organic-inorganic nano hybrid fiber membrane. On the other hand, since the interlayer of the nano vermiculite is opened, the absorption of heat is enhanced, the thermal conductivity decreases, and its thermal insulation and fireproof properties are enhanced, so that the flame retardant properties of the organic-inorganic nano hybrid fiber membrane are significantly enhanced. In Comparative Example 1, the vermiculite was not peeled off by mechanical and chemical action, its interlayers were not opened, and nano vermiculite was not formed. Therefore, the catalytic activity was weak, resulting in poor catalytic hydrolysis of cellulose and low yield of nano cellulose. Moreover, the vermiculite size was at the micron scale, and its dispersion performance in the nano cellulose solution was not good, resulting in the formed organic-inorganic nano hybrid fiber membrane having mechanical properties inferior to those in the embodiment, and the vermiculite's heat absorption capacity was inferior to that of nano vermiculite. Therefore, the flame retardant performance of the organic-inorganic nano hybrid fiber membrane was inferior to that in the embodiment.
[0043] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A one-pot method for preparing high-strength, flame-retardant organic-inorganic nano-hybrid fiber membranes, characterized in that: The following steps are involved: (1) adding heat-expanded vermiculite to a saturated sodium chloride solution for colloidal mill pretreatment, and then adding a hydrochloric acid solution for microwave-ultrasonic reaction to obtain a nano-vermiculite solution; (2) adding cellulose raw material to the nano-vermiculite solution obtained in step (1), adjusting the reaction temperature, and continuing the microwave-ultrasonic reaction to obtain nano-cellulose, and uniformly dispersing the collected reaction product by ultrasonication to form a nano-vermiculite / nano-cellulose mixed solution; (3) injection molding the nano-vermiculite / nano-cellulose mixed solution obtained in step (2), and drying it under constant temperature and humidity conditions to form a film, immersing the formed film in deionized water and repeatedly rinsing it to remove inorganic salt ions, and naturally drying it at room temperature to obtain a high-strength, flame-retardant organic-inorganic nano-hybrid fiber membrane; In step (1), the solid-liquid ratio of the heat-expanded vermiculite to the saturated sodium chloride solution is 1:25-1:50 g / mL, the rotation speed of the colloid mill is 10000-13000 rpm, and the colloid mill pretreatment time is 6-11 hours; the concentration of the hydrochloric acid solution used is 0.1-0.5 mol / L, the solid-liquid ratio of the heat-expanded vermiculite to the hydrochloric acid solution is 1:60-1:80 g / mL, the microwave power is 600 W, the ultrasonic power is 800 W, the microwave-ultrasonic reaction time is 9 hours, and the reaction temperature is 120°C; In step (2), the solid-liquid ratio of the cellulose raw material to the nano-vermiculite solution is 1:25-1:50 g / mL; the microwave-ultrasonic reaction time is 4 hours, the reaction temperature is 100° C., the microwave power is 500 W, and the ultrasonic power is 800 W.
2. The one-pot method for preparing high-strength, flame-retardant organic-inorganic nano-hybrid fiber membrane according to claim 1, characterized in that: The cellulose raw material in step (2) is any one of coniferous wood pulp, broadleaf wood pulp and bamboo pulp.
3. The one-pot method for preparing high-strength, flame-retardant organic-inorganic nano-hybrid fiber membrane according to claim 1, characterized in that: The constant temperature and humidity conditions in step (3) are 50°C, 50% humidity, and 24h drying time.